Association between circulating vascular-related microRNAs and an increase in blood pressure: a 5-year longitudinal population-based study. Issue 1 (January 2021) - Suzuki, Koji; Yamada, Hiroya; Fujii, Ryosuke; Munetsuna, Eiji; Ando, Yoshitaka; Ohashi, Koji; Ishikawa, Hiroaki; Yamazaki, Mirai; Maeda, Keisuke; Hashimoto, Shuji; Hamajima, Nobuyuki
Abstract : Objective: MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression and play essential roles in the pathogenesis of cardiovascular disease. Previous cross-sectional studies showed that the levels of several circulating miRNA are associated with hypertension, but there are no prospective longitudinal studies using a general population. The aim of this study is to evaluate the impact of circulating vascular-related miRNA (miR-126, miR-221, and miR-222) on changes in blood pressure and new-onset hypertension in a Japanese population. Methods: We conducted a 5-year longitudinal study using 192 health examination participants (87 men and 105 women). Serum miRNAs were measured using quantitative reverse transcription-PCR. Information regarding lifestyle and health condition was obtained using a self-administered questionnaire. Logistic regression analyses were performed to calculate odds ratios and 95% confidence intervals for new-onset hypertension in the 5-year period between the low and high group of serum miRNAs. Results: Serum levels of miR-126, miR-221, and miR-222 were significantly and negatively associated with changes in SBP and the rate of change of SBP. Serum miR-126, miR-221, and miR-222 levels were significantly lower in new-onset hypertensive patients compared with normotensive individuals. The confounding factors adjusted odds ratios of each 1 increment in serum miR-126, miR-221, and miR-222 levels were 0.82 (95% confidence interval: 0.69–0.98), 0.79 (0.68–0.91), and 0.61 (0.46–0.81) for new-onset hypertension, respectively. Conclusion: Low serum levels of miR-126, miR-221, and miR-222 were associated with increased blood pressure and new-onset of hypertension. These circulating miRNAs are potential candidate biomarkers for the prediction of hypertension.